2020
DOI: 10.1371/journal.pone.0228336
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic inequities in the associations of allostatic load with all-cause and cardiovascular-specific mortality risk in U.S. adults

Abstract: Non-Hispanic blacks have higher mortality rates than non-Hispanic whites whereas Hispanics have similar or lower mortality rates than non-Hispanic blacks and whites despite Hispanics' lower education and access to health insurance coverage. This study examines whether allostatic load, a proxy for cumulative biological risk, is associated with all-cause and cardiovascular (CVD)-specific mortality risks in US adults; and whether these associations vary with race/ethnicity and further with age, sex and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Measuring lead in plasma may also have improved the study, as plasma lead levels may better reflect Pb that is more freely available for exchange with target tissues than Pb levels in whole blood [ 71 ]. Also, AL may not fully capture the experience and full impact of chronic stress related to health; however, it offers critical insight and is an accepted method to use with NHANES data [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring lead in plasma may also have improved the study, as plasma lead levels may better reflect Pb that is more freely available for exchange with target tissues than Pb levels in whole blood [ 71 ]. Also, AL may not fully capture the experience and full impact of chronic stress related to health; however, it offers critical insight and is an accepted method to use with NHANES data [ 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the HPA axis, critical for regulating neuroendocrine system responses to stressful stimuli, has been associated with cardiovascular dysfunction [ 22 ]. AL offers vital insight into the effects of chronic stress on health outcomes [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obstacles for healthcare access in older adults have been consistently associated with worsened outcomes and increased all-cause mortality, particularly for those facing social inequalities [27]. Previous research has shown that negative self-perceived aging influences healthcare-seeking behavior, particularly in settings of limited healthcare access [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term impact on organ systems, including metabolic (e.g., triglycerides), neuroendocrine (e.g., cortisol), immune (e.g., CRP), and cardiovascular (e.g., blood pressure), results in significant long-term consequences to health (Borrell et al, 2020;Forde et al, 2019;Juster et al, 2010;Samuel et al, 2018).…”
Section: Stress African American Caregivers and Health Outcomesmentioning
confidence: 99%